2020
DOI: 10.1371/journal.pone.0228353
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers of Carex (Cyperaceae) and their taxonomic implications

Abstract: Counting chromosomes is the first step towards a better understanding of the karyotype evolution and the role of chromosome evolution in species diversification within Carex; however, the chromosome count is not known yet for numerous sedges. In this paper chromosome counts were performed for 23 Carex taxa from Armenia, Austria, the Czech Republic, and Poland. Chromosome numbers were determined for the first time in three species (Carex cilicica, 2n = 54; C. phyllostachys, 2n = 56; C. randalpina, 2n = 78), two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In the Cyperaceae family, which is the largest group of holocentric plants, chromosomes vary from n = 2 to n = 108 (Roalson, 2008). Although the lowest chromosome number in angiosperms is found in Rhynchospora tenuis (n = 2), we can also find extraordinarily very high chromosomes numbers in other genera within this family, for instance in Carex (Wieclaw et al, 2020) and Cyperus (Roalson, 2008). Since the number of chromosomes is proportional to recombination rates, high chromosome numbers would also impose higher recombination rates in holocentric plants, specially, in this case where the number of chiasmata tends to be typically low, with one or two CO per bivalent.…”
Section: Meiotic Recombination In Holocentric Plantsmentioning
confidence: 68%
“…In the Cyperaceae family, which is the largest group of holocentric plants, chromosomes vary from n = 2 to n = 108 (Roalson, 2008). Although the lowest chromosome number in angiosperms is found in Rhynchospora tenuis (n = 2), we can also find extraordinarily very high chromosomes numbers in other genera within this family, for instance in Carex (Wieclaw et al, 2020) and Cyperus (Roalson, 2008). Since the number of chromosomes is proportional to recombination rates, high chromosome numbers would also impose higher recombination rates in holocentric plants, specially, in this case where the number of chiasmata tends to be typically low, with one or two CO per bivalent.…”
Section: Meiotic Recombination In Holocentric Plantsmentioning
confidence: 68%
“…Meiotic aberrations are also quite common in Carex and can cause these taxa to behave unlike most other angiosperms, especially with regard to hybridization (Hipp, 2007). There are no chromosome count data available for either of the parental species; counts in the genus range from n = 6–62 (Więcław et al, 2020), limiting our ability to consider the viability of this alternative explanation for the outlier loci. However, it seems peculiar that we observed a similar number of loci with extreme ancestry for each parent; this is consistent with a drift hypothesis, but the environmental association of outlier loci and their position in environmental space makes this unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…buxbaumii , and 2n = 52, 68 for C . hartmaniorum (see Więcław, Kalinka & Koopman, 2020 ). Generally, polyploidy in Carex is relatively rare and is fairly difficult to find due to chromosomal traits (i.e., holocentric chromosomes) ( Hipp, Rothrock & Roalson, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipnerová et al (2013) demonstrated that a substantial increase in the chromosome count (mostly doubling) corresponded with a concomitant increase in the genome size in the sections Clandestinae and Racemosae; in the latter, the genome size and the chromosome counts in C. buxbaumii and C. adelostoma were almost twice those in C. aterrima, C. parviflora, C. atrata, C. norvegica and C. hartmaniorum. Moreover, the species were referred to as having different cytotypes; mainly 2n = 100, 102, 106 for C. buxbaumii, and 2n = 52, 68 for C. hartmaniorum (see Więcław, Kalinka & Koopman, 2020). Generally, polyploidy in Carex is relatively rare and is fairly difficult to find due to chromosomal traits (i.e., holocentric chromosomes) (Hipp, Rothrock & Roalson, 2009).…”
Section: Variability Within Carex Buxbaumii Populationsmentioning
confidence: 99%